Role-emerging Placements: a Useful Model for Occupational Therapy Practice Education? A Review of the Literature - Clarke, Channine; de Visser, Richard; Martin, Marion; Sadlo, Gaynor (International Journal of Practice-based Learning in Health and Social Care, 2016)
Changes in health and social care present exciting opportunities for occupational therapists in the United Kingdom to expand their practice into innovative settings. To prepare graduates for these opportunities, placement experiences must reflect current trends in practice. Role-emerging placements are increasingly being used within occupational therapy to help students develop the skills, knowledge and attributes needed to become the therapists of tomorrow. This paper provides an overview of the literature on the use of role-emerging placements within the profession by considering the current context of placements, the rationale for the development of role-emerging placements and their potential strengths and limitations. The paper aims to increase awareness in the UK of role-emerging placements and their potential value within health and social care education.